Use of the Neurospora tyrosinase gene as a reporter gene in transformation experiments - Gregory O. Kothe; Maria Deak; Stephen J. Free (Fungal Genetics Reports, 1993)
Reporter gene systems have been developed to allow investigators to visually identify transformed cells and to follow the transcriptional activity from promoter regions preceding the reporter genes. These reporter genes encode protein products which can be easily assayed and which can be strained for in the transformed cell.